Improvements in Plasma Tumor Necrosis Factor-Alpha Levels after a Weight-Loss Lifestyle Intervention in Patients with Obstructive Sleep Apnea - Michael Georgoulis; Nikos Yiannakouris; Roxane Tenta; Ioanna Kechribari; Kallirroi Lamprou; Emmanouil Vagiakis; Meropi D. Kontogianni (Life, 2022)
Obstructive sleep apnea (OSA) and systemic inflammation typically coexist within a vicious cycle. This study aimed at exploring the effectiveness of a weight-loss lifestyle intervention in reducing plasma tumor necrosis factor-alpha (TNF-a), a well-established modulator of systematic inflammation in OSA. Eighty-four adult, overweight patients with a diagnosis of moderate-to-severe OSA were randomized to a standard care (SCG, n = 42) or a Mediterranean lifestyle group (MLG, n = 42). Both groups were prescribed continuous positive airway pressure (CPAP), while the MLG additionally participated in a 6-month behavioral intervention aiming at healthier weight and lifestyle habits according to the Mediterranean pattern. Plasma TNF-a was measured by an immunoenzymatic method both pre- and post-intervention. Drop-out rates were 33% (n = 14) for the SCG and 24% (n = 10) for the MLG. Intention-to-treat analysis (n = 84) revealed a significant decrease in median TNF-a only in the MLG (from 2.92 to 2.00 pg/mL, p = 0.001). Compared to the SCG, the MLG exhibited lower follow-up TNF-a levels (mean difference adjusted for age, sex, baseline TNF-a and CPAP use: −0.97 pg/mL, p = 0.014), and further controlling for weight loss did not attenuate this difference (p = 0.020). Per protocol analyses (n = 60) revealed similar results. In conclusion, a healthy lifestyle intervention can lower plasma TNF-a levels in patients with OSA.